Augmented reality as a participation tool for youth in urban planning processes: Case study in Oslo, Norway - Reaver, Kai (Frontiers in Virtual Reality, 2023)
Augmented reality (AR) allows objects to be digitally simulated in the real world through smartphones, tablets, and headsets. While there are interesting AR technology case studies in participatory urban planning, this type of research has yet to be conducted within a real-life municipal planning scenario. Following the UN Habitat recommendation that further studies in AR as a participatory tool seek to integrate planning with real citizens, we studied the use of AR for the Oslo Trees plan in Norway. The case study consists of field work with AR between 2020 and 2021 over five weeks, with five different groups of youth participants from eight different districts of Oslo, who were tasked with planning a portion of Oslo’s 100,000 new trees. We document how these youths used AR in films, images, drawings, interviews, screen recordings, and recorded presentations. We find that AR is a highly intuitive tool for these youth user groups in design and planning and how the AR schemes impacted the final design of the plan. The use of AR aided users’ ability to generate their own planning proposals on site at scale; nearly all participants increased their understanding of participation, urban planning, architecture, and design in the workshops. In addition, the youths experienced an increased sense of confidence in displaying their design intentions and appreciated being given control of the planning process. However, we also found that location tracking and positioning in AR is imprecise and often “buggy” in the current state of the technology, causing irritation among users. Furthermore, despite the high degree of control afforded to users through AR, experts were still needed to verify which tree proposals were viable, offering important insights into how AR could be designed in the future. We conclude with a discussion on opportunities and barriers for the implementation of AR in participatory urban planning, pointing to the need for a more coordinated and holistic approach to both AR technology development and planning policy if the technology is to be developed further for participatory urban planning.